Early life stress is a risk factor for excessive alcohol drinking and impulsivity in adults and is mediated via a CRF/GABAA mechanism. (3rd March 2016) - Gondré-Lewis, Marjorie C.; Warnock, Kaitlin T.; Wang, Hong; June, Harry L.; Bell, Kimberly A.; Rabe, Holger; Tiruveedhula, Veera Venkata Naga Phani Babu; Cook, James; Lüddens, Hartmut; Aurelian, Laure; June, Harry L.
Abstract: Childhood stress and trauma are associated with substance use disorders in adulthood, but the neurological changes that confer increased vulnerability are largely unknown. In this study, maternal separation (MS) stress, restricted to the pre-weaning period, was used as a model to study mechanisms of protracted effects of childhood stress/traumatic experiences on binge drinking and impulsivity. Using an operant self-administration model of binge drinking and a delay discounting assay to measure impulsive-like behavior, we report that early life stress due to MS facilitated acquisition of binge drinking and impulsivity during adulthood in rats. Previous studies have shown heightened levels of corticotropin releasing factor (CRF) after MS, and here, we add that MS increased expression levels of GABAA α2 subunit in central stress circuits. To investigate the precise role of these circuits in regulating impulsivity and binge drinking, the CRF1 receptor antagonist antalarmin and the novel GABAA α2 subunit ligand 3-PBC were infused into the central amygdala (CeA) and medial prefrontal cortex (mPFC). Antalarmin and 3-PBC at each site markedly reduced impulsivity and produced profound reductions on binge-motivated alcohol drinking, without altering responding for sucrose. Furthermore, whole-cell patch-clamp studies showed that low concentrations of 3-PBC directly reversed the effect of relatively high concentrations of ethanol on α2β3γ2 GABAA receptors, by a benzodiazepine site-independent mechanism. Together, our data provide strong evidence that maternal separation, i.e. early life stress, is a risk factor for binge drinking, and is linked to impulsivity, another key risk factor for excessive alcohol drinking. We further show that pharmacological manipulation of CRF and GABA receptor signaling is effective to reverse binge drinking and impulsive-like behavior in MS rats. These results provide novel insights into the role of the brain stress systems in the development of impulsivity and excessive alcohol consumption.